Input Power Quality Enhancement in Controlled Single-Phase AC to DC Converter - Naveed Ashraf; Ghulam Abbas; Tanveer Yazdan (Energies)
Voltage-controlled AC to DC converters govern the load voltage as per requirement. They may be employed in numerous applications, including battery-charging systems, light dimming, and industrial speed drive systems. The voltage regulation is based on the delay angle control of the thyristors, which has a simple gate control mechanism. Still, their input currents are highly distorted due to the generation of low-order harmonics. Also, their output voltage can only be regulated in step-down mode. The total harmonic distortion (THD) of the input current depends on the relative value of the fundamental frequency components to their non-fundamental component. The power factor (PF) also depends on these values, as well as the phase displacement angle, which is controlled by the firing delay. The improvement in THD and PF can be enhanced by maintaining the sinusoidal characteristics of the input current as much as possible. The use of an AC filter may enhance these characteristics, but filtering the low-order harmonics is a big challenge. This research suggests a novel control and circuit of a single-phase rectifier that may ensure the sinusoidal characteristics of the input current with a dual polarity-controlled output voltage. Thus, it improves the THD and PF for any polarity of the output DC voltage. A practical test circuit is built for the validation of the analytical and computer simulation results.